The Relationship Between Poverty, Income Inequality, and Hunger in Indonesia: A Sustainable Economic Approach Systematic Literature Review - Supriadi Siagian; Durahman Marpaung; Prianda Pebri; Taufiq Hidayah; Purwanto Purwanto; Fandra Dikhi Januardani; Sabrina Sabrina (International Journal of Management, Accounting & Finance (KBIJMAF), 2025)
The persistent challenge of hunger remains a critical obstacle to achieving sustainable development in Indonesia, where socioeconomic inequality, environmental degradation, and unstable food systems continue to limit progress toward Sustainable Development Goal 2 (Zero Hunger). This study systematically reviews international and national literature published between 2018 and 2024 to identify the key sustainable economic strategies that effectively address hunger in Indonesia. Guided by the PRISMA 2020 protocol, the review integrates 62 eligible studies sourced from Scopus, Web of Science, ERIC, and Google Scholar databases. Findings reveal that circular economy practices, green innovation, and climate-smart agriculture play central roles in improving food availability, reducing post-harvest losses, and enhancing community resilience. Furthermore, digital transformation and inclusive economic policies are shown to strengthen food supply chains and ensure equitable access to resources. The discussion emphasizes the interdependence between economic sustainability, social equity, and environmental stewardship as pillars of hunger reduction. The study concludes by proposing a policy framework that aligns national development strategies with sustainable agricultural innovation and resilience-based economic systems. This framework is expected to guide policymakers in strengthening Indonesia’s.